THE APPLICATION OF THE HYBRID CONTRACTS CONCEPT TO MULTIPURPOSE FINANCING - Burhanudin, Muhammad (Journal of Economicate Studies, 2018)
The term hybrid contracts (al-ququd al-murakkabah / multiakad) are already familiar to practitioners and academics of sharia economic law. This indicates the rapid innovation in sharia economic law, especially in sharia financial institutions. Each product issued by Islamic financial institutions certainly uses more than one contract, including multipurpose financing products. Then what about the hadith narrated by Imam Ahmad who stated "... has prohibited two agreements (contract) in one agreement (contract) ...". Is multipurpose financing including prohibited or not? To answer this question, the author tries to examine more comprehensively about the application of the concept of hybrid contracts to Multipurpose Financing. The results of the author's analysis suggest the following: first, that in its implementation, multipurpose financing applied in Islamic banking uses a hybrid contracts (al-‘uqud al-murakkabah / multiakad). The contracts applied to this multipurpose financing are murabahah contracts, ijarah contracts, and kafalah contracts; second, the application of hybrid contracts in multipurpose financing turns out as long as it does not conflict with the rules in Law Number 21 of 2008 concerning Islamic Banking and does not conflict with the MUI DSN Fatwa on Murabahah, Ijarah and Kafalah, and does not conflict with the Compilation of Islamic Economic Law (KHES), therefore, the application of these hybrid contracts is permissible. and third, as for the object of multipurpose financing in the form of halal goods and / or services (allowed by sharia), including financing to meet customer needs for halal goods / objects, in addition to land and residential buildings, flats (apartments, shop houses, home office) cars and gold. The financing objects that are allowed include: two-wheeled motorcycles, building materials, electronic goods, household furniture. These objects are not necessarily the same as those applied to other banks.